Risk of breast cancer and other cancers in heterozygotes for ataxia-telangiectasia. - Inskip, H; Kinlen, L; Taylor, A; Woods, C; Arlett, C (1999)
Mortality from cancer among 178 parents and 236 grandparents of 95 British patients with ataxia-telangiectasia was examined. For neither parents nor grandparents was mortality from all causes or from cancer appreciably elevated over that of the national population. Among mothers, three deaths from breast cancer gave rise to a standardized mortality ratio of 3.37 (95% confidence interval (CI): 0.69-9.84). In contrast, there was no excess of breast cancer in grandmothers, the standardized mortality ratio being 0.89 (95% CI: 0.18-2.59), based on three deaths. This is the largest study of families of ataxia-telangiectasia patients conducted in Britain but, nonetheless, the study is small and CIs are wide. However, taken together with data from other countries, an increased risk of breast cancer among female heterozygotes is still apparent, though lower than previously thought.